The DNA replication checkpoint targets the kinetochore to reposition DNA structure-induced replication damage to the nuclear periphery - Tyler M. Maclay; Jenna M. Whalen; Matthew J. Johnson; Catherine H. Freudenreich (Cell Reports)
Summary: Hairpin-forming CAG/CTG repeats pose significant challenges to DNA replication. In S. cerevisiae, long CAG/CTG repeat tracts reposition from the interior of the nucleus to the nuclear pore complex (NPC) to maintain their integrity. We show that relocation of a (CAG/CTG)130 tract to the NPC is dependent on phosphorylation of Mrc1 (hClaspin) of the fork protection complex and activation of the Mrc1/Rad53 replication checkpoint, implicating an uncoupled fork as the initial damage signal. Dun1-mediated phosphorylation of the kinetochore protein Cep3 is required for repositioning, a constraint that can be overcome by centromere inactivation, connecting detachment of the kinetochore from microtubule ends to NPC association. Activation of this pathway leads to the formation of DNA damage-induced microtubules, which associate with the repeat and are necessary for locus repositioning. These data implicate the replication checkpoint in facilitating the movement of DNA structure-associated damage to the nuclear periphery by centromere release and microtubule-directed motion.